Complex Fiber Micro-Knots - Shahal, Shir (Sensors (Basel), 2018)
Fiber micro-knots are a promising and a cheap solution for advanced fiber-based sensors. We investigated complex fiber micro-knots in theory and experiment. We compared the measured spectral response and present an analytical study of simple micro-knots with double twists, twin micro-knots, figure-eight micro-knots, and tangled micro-knots. This research brings the simple fabrication process and robustness of fiber micro-knots into the world of complex resonators which may lead to novel optical devices based on fiber micro-knots.